The circulation at high altitudes - Rotta, Andrés (1938)
We have explored a set of features circularias 18 Morococha native subjects (4.538 meters), comparing the results with previous research and the same characters studied at sea level in 22 healthy men. This comparative study has showed some modifications of the circulatory function of the inhabitants of the height, whose character and significance summarily discussed. In one group of animals (dogs) at sea level and at another height have practiced some observations on circulatory function. The results indicate that the compensation mechanisms, from the point of view circulatory are identical that in man.